Establishment and operation of a Good Manufacturing Practice‐compliant allogeneic Epstein‐Barr virus (EBV)‐specific cytotoxic cell bank for the treatment of EBV‐associated lymphoproliferative disease. (26th July 2014) - Vickers, Mark A.; Wilkie, Gwen M.; Robinson, Nicolas; Rivera, Nadja; Haque, Tanzina; Crawford, Dorothy H.; Barry, Jacqueline; Fraser, Neil; Turner, David M.; Robertson, Victoria; Dyer, Phil; Flanagan, Peter; et al.
Summary Epstein‐Barr virus (EBV) is associated with several malignancies, including post‐transplant lymphoproliferative disorder (PTLD). Conventional treatments for PTLD are often successful, but risk organ rejection and cause significant side effects. EBV‐specific cytotoxic T lymphocytes (CTLs) generated in vitro from peripheral blood lymphocytes provide an alternative treatment modality with few side effects, but autologous CTLs are difficult to use in clinical practice. Here we report the establishment and operation of a bank of EBV‐specific CTLs derived from 25 blood donors with human leucocyte antigen (HLA) types found at high frequency in European populations. Since licensure, there have been enquiries about 37 patients, who shared a median of three class I and two class II HLA types with these donors. Cells have been infused into ten patients with lymphoproliferative disease, eight of whom achieved complete remission. Neither patient with refractory disease was matched for HLA class II. Both cases of EBV‐associated non‐haematopoietic sarcoma receiving cells failed to achieve complete remission. Thirteen patients died before any cells could be issued, emphasizing that the bank should be contacted before patients become pre‐terminal. Thus, this third party donor‐derived EBV‐specific CTL cell bank can supply most patients with appropriately matched cells and most recipients have good outcomes.